CORRELATION BETWEEN SELF-ESTEEM AND ENGLISH ACHIEVEMENT TO THE TENTH GRADE STUDENTS OF SMAN 03 KETAPANG IN THE ACADEMIC YEAR OF 2015-2016 - Gusti Muhammad Randa (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura)
This research was aimed to find out the correlation between self-esteem and students' English achievement. This research was conducted through correlational design. The sample was the tenth-grade students of SMA N 03 Ketapang in the academic year of 2015-2016. The sample was taken using disproportionate stratified random sampling which took five students each class from eight classes, there were forty students in the sample. This research used indirect communication as the technique of data collection. The tools of data collection were a questionnaire and school document. The data analysis used in this research was statistical analysis. To find out the relationship between both variables, Pearson Product Moment formula was used. It showed that there is a positive correlation between the two variables with the significant of correlation is 0.374 which is categorized as moderate correlation. Then, as the level of self-esteem increases, the level of students' English achievement also increases